Minimasi Pemborosan pada Lantai Produksi PT Kunango Jantan dengan Pendekatan Lean Manufacturing - Rahmayanti, Dina; Qomariah, Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT Kunango Jantan is one of the private companies engaged in manufacturing and trading. One of the products produced is Street Light Pole (PJU). The production of these PJU poles also faces various challenges. Commonly faced challenges are related to several types of waste on the production floor. This research aims to identify waste on the production floor of PJU poles using a lean manufacturing approach. The results indicate that the top three waste percentages are 18.9% for transportation activities, 17.62% for waiting activities, and 15.46% for defects. Some factors causing these wastages include frequent machine breakdowns, depletion of raw materials due to the lack of raw material scheduling implementation, and frequent transportation during production. Improvement recommendations to reduce waste include scheduling machine maintenance, planning raw material control, and adjusting machine layouts to minimize repetitive transportation.